Kant and the meaning of religion: the critical philosophy and modern religious thought - Godlove, Terry F. (Library of modern religion, 2014)
Kant and Religion is a subtle and penetrating attempt, by a leading contemporary philosopher of religion, to redefine and reshape the contours of his own discipline through sustained reflection on Kant's so-called 'humanizing project'